Interaksi Faktor Umur dan Musim terhadap Kualitas Semen Pejantan Kambing Peranakan Etawa dan Boer - Fariz Zharfan Haris (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2026)
Male reproductive performance serves as a foundational metric for predicting the reproductive quality traits of progeny. This study aimed to investigate the interaction between semen quality in Etawa Grade (PE) and Boer bucks and non-genetic factors, specifically age and season. The research utilised secondary data on fresh semen production collected from 2018 to 2022. Quality parameters evaluated included ejaculate volume and individual sperm motility. Data were obtained from the Central Java Artificial Insemination Center and analysed using the Statistical Analysis System On Demand for Academics to determine the interactive effects of age and season on fresh semen production. The results indicated that bucks in the younger age category tended to produce higher semen volumes compared to other age groups. In conclusion, there is a general interaction between age and season on the semen quality of PE and Boer bucks. The interaction observed in fresh semen volume and motility was significantly influenced by individual age differences and seasonal factors based on rainfall levels. Further research is warranted to investigate these interactions across additional macroscopic and microscopic parameters.